Synthesis and Characterization of Piezotronic Materials for Application in Strain/Stress Sensing - Zhu, Ren (Mechanical Engineering Series,, 2018)
This book explores the new materials and the resultant new field of piezotronics. The growth and alignment of the zinc oxide nanostructures are discussed in detail because of its wide adoption in this field and its significance in optics, health, and sensing applications. The characterization of the piezotronic effect and how to distinguish it from other similar but, fundamentally different effects, like piezoresistive effect is also considered. The huge potential in the wearable and flexible devices, as well as organic materials, is further examined. The stain/stress sensing is introduced as an example of an application with piezotronic materials. Presents a comprehensive review of the new field of piezotronics; Illustrates how to distinguish the piezotronic effect from other, similar physical phenomena; Explains how to develop novel electronic devices with piezotronic materials; Introduces the organic piezotronic materials for the first time.